2017
DOI: 10.3390/atmos8040079
|View full text |Cite
|
Sign up to set email alerts
|

Application of Convective Condensation Level Limiter in Convective Boundary Layer Height Retrieval Based on Lidar Data

Abstract: Abstract:Micro pulse lidar is a promising tool for retrieving the convective boundary layer height (CBLH), but its application has been hindered by sharp extinction of the signal in high humidity conditions, e.g., clouds. To remedy this, we developed an effective and simple limiter to obtain more accurate estimates of the CBLH. The limiter is based on the algorithm for the convective condensation level (CCL) and is aimed at limiting the vertical extent of the lidar backscatter profile used in lidar methods to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Thus, the information of the upper aerosol layers will be omitted, however, the operation is not suited when the cloud base is lower than the top of ML. Li et al [126] used the convective condensation height (CCL) to estimate the base of clouds that are decoupled from the ABL, only the RSCS below the CCL are used to eliminate the interference of clouds. This method is a good choice in cloudy situations if thermodynamic profiles are available when CCL can be accurately calculated.…”
Section: Height Restriction For Some Classical Methodologiesmentioning
confidence: 99%
“…Thus, the information of the upper aerosol layers will be omitted, however, the operation is not suited when the cloud base is lower than the top of ML. Li et al [126] used the convective condensation height (CCL) to estimate the base of clouds that are decoupled from the ABL, only the RSCS below the CCL are used to eliminate the interference of clouds. This method is a good choice in cloudy situations if thermodynamic profiles are available when CCL can be accurately calculated.…”
Section: Height Restriction For Some Classical Methodologiesmentioning
confidence: 99%
“…In recent years, laser-based remote sensing instruments, especially automatic LiDARs and ceilometers (ALC), have become more affordable and widely used in the field of atmospheric research, particularly for MLH determination [38][39][40][41][42][43][44][45]. We should also note the considerable efforts made in the COST Action ES 1303 TOPROF [46] which provides standards for calibrated profiles of the aerosols, winds, temperature, and humidity to fill the observational gap in the lower troposphere.…”
Section: Introductionmentioning
confidence: 99%
“…An example of an NRB profile with the shape of a Haar wavelet and the profile of the covariance transform is shown as Figure 1; the determined ABLH is approximately 2000 m. The selection of ∆h is key to successfully determining the ABLH. Li [46,49] showed that an appropriate value of ∆h = 200∆z = 300 m (∆z is the vertical resolution of the NRB, which is 15 m) is suitable for HM over SACOL. The lidar data used in this study was collected from the same observation site, and the initial value of the parameter, ∆h, is valued as 300 m. lidar signal to isolate the spikes due to aerosol concentrations.…”
Section: Traditional Techniquesmentioning
confidence: 99%
“…However, Cimini [45] indicates that correctly identifying the ABLH among height retrieved with key gradients is ambiguous when using lidar data alone, meaning that other complementary methods (such as the variance-based method in [38]) or additional observations (such as the brightness temperature information in [45]) are required. Li [46] retrieved the ABLH from lidar data during cloudy conditions using the objective upper limit of the convective condensation level (CCL). Only the lidar signal below the CCL are utilized to retrieve the CBL height (CBLH).…”
Section: Introductionmentioning
confidence: 99%